Morphology evolution of P-Ti3AlC carbides and their influence on creep properties in a crept Ti-45Al-5Nb-0.75C alloy - Xianli Cao; Li Wang; Hui Tao; Weiwei He; Xiaopeng Liang; Bin Liu; Michael Oehring; Jonathan Paul; Florian Pyczak; Yong Liu (Journal of Materials Research and Technology, 2024)
In this study, the influence of the Ti3AlC carbide morphology on the creep properties, the interaction between carbides and dislocations during creep deformation as well as the influence of external stress on carbide morphology evolution were investigated in a Ti-45Al-5Nb-0.75C alloy. The results show that the best creep properties are obtained after annealing at 800 °C for 336 h. This is probably due to the splitting of the carbides into conglomerates of sub-particles, which provides an increased number of interfacial area and interfaces to hinder dislocation glide. After prolonged annealing for 1054 h at 800 °C, although the carbide splitting still existed, the matrix grains coarsened and the lamellar structure was decomposed, which counteracted the positive effect of carbide splitting and led to a reduction in the creep resistance. By comparing the carbide morphology evolution after creep and after annealing alone, it can be concluded that the external stress does not significantly affect the morphology evolution. During creep at 800 °C the Ti3AlC carbides obviously interact with dislocations, and the majority of them were identified to be ½<110] ordinary dislocations. The glide of these dislocations was strongly hindered, and thus the creep properties of the alloy can be improved by carbide precipitation.